Nicotine dependence and quit smoking: a preliminary survey among adult males in Kuantan, Malaysia - SweSwe , Latt; Razman, Mohd. Rus; Jamalludin, Ab Rahman; Nasreen, Hashima E; Karimah Hanim, Abdul aziz; Htike Myat , Phyu (Faculty of Medicine, International Islamic University Malaysia, 2015)
Introduction: Most of the smokers remain as active smokers and unrecognized their nicotine dependence (ND) level. ND was an important reason to addict smoking. The study determined the prevalence of smoking and ND among adult males and their difficulties to quit smoking. Methods: A cross-sectional study was conducted among 296 males aged 18 years and above from Felda Bukit Goh at Kuantan, Malaysia in 2015. Socio-economic status, history of smoking, quit attempt and reasons for failing quit were explored by using a self-administered questionnaire. Level of ND was assessed by validated Malay version of Fagerstrom Test for ND questionnaires. Stratified analysis on relationship among socio-economic status and current smoking status, level of ND was done. Results: The prevalence of current smokers was 61.1% and the prevalence of low and moderate to high ND level was 76.2 % and 23.8 % respectively. Among them 54.1% of smokers were tried to quit smoking ranging from 1 to 30 times by self-awareness (48%) and their main reason to fail was addiction (71.9%). Smokers with monthly household income (RM2000-2999) was independently associated with moderate to high ND with AOR=4.73 (95% CI 1.83-12.18) compared to those with income (less than RM2000). Conclusion: Despite high prevalence of smoking, majority of smokers have low ND and addiction was the main reason to fail quit attempt. Household income was a contributing factor for moderate to high ND. The finding provides hope for the success of smoking cessation programme if it is to be done in this locality.